ANALISIS DINAMIS PERMINTAAN DAN PENAWARAN KOMODITAS KEDELAI DI JAWA TIMUR - Rifa’i, Muhammad (IQTISHODUNA, 2010)
The aims of this research are: (a) analyze factors influenceing supllay, import and demand of soybean in east java region; (b) analyze factors influencing price of soybean; (c) analyze linkage among suplay, import, demand and domistic price of soyben simultaneously. This research conducted in east java as main producer of soyben in Indonesia. We use secondary data for 1980-2004 periods wits simutaneus models, especially two stage least square method. The result of research shows that the model of demand and supply used had fulfilling economic, statistic and econometric criteria so can be used to explain economic behavior of soyben in east java correctly. Suplay of soybean influenced positively by corn price, productivity and harvesting are of soybean commodity, while domistic price of soybean, price of rice, price of fertilizer, world price and so lags of supplay does not significant. Import positively influenced by income and current demand, and negatively import does not significant. Domistic demand of soybean positively influenced by population size and negatively influenced influenced by per capita income, while other variables such as domistic price, corn price and previous demand does not significant. Domistic price positively influenced by suplay and exchange rate, and so previosly domistic price, while demand and world price does not signficant.